KEWENANGAN NOTARIS DALAM MEMBUAT SURAT KETERANGAN WARIS BERDASARKAN PENGGOLONGAN PENDUDUK UNTUK PENDAFTARAN TANAH DI INDONESIA - Adek Junjunan Syaid (VERITAS, 2017)
This journal discusses the heir statement as a document used to prove one's position as heir. Certificate of Inheritance issued by official or government authorities or made by the heirs can be used as strong evidence of the existence of a transitional land rights of a property left by the deceased. The purpose of this study was to determine and analyze the authority in making a Notary Certificate of Inheritance based classification Residents To Pndaftaran Land in Indonesia and the legal consequences of the Notary who makes a Certificate of Inheritance based classification Residents to Register Land in Indonesia. In the discussion can be developed an analysis that the legal system in Indonesia is a former colony of the Dutch colonial government in terms of inheritance system until now still being enforced. Enabling the system is not only substasinya alone but also the spirit that oppress and exploit. Indonesia as an independent country, a civilized, equitable, and uphold Human Rights (HAM) as if it had been ruled out and contrary to the philosophy of the Indonesian state.